If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(y + -3) = y + 4s Reorder the terms: -2(-3 + y) = y + 4s (-3 * -2 + y * -2) = y + 4s (6 + -2y) = y + 4s Reorder the terms: 6 + -2y = 4s + y Solving 6 + -2y = 4s + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 6 + -2y + -1y = 4s + y + -1y Combine like terms: -2y + -1y = -3y 6 + -3y = 4s + y + -1y Combine like terms: y + -1y = 0 6 + -3y = 4s + 0 6 + -3y = 4s Add '-6' to each side of the equation. 6 + -6 + -3y = -6 + 4s Combine like terms: 6 + -6 = 0 0 + -3y = -6 + 4s -3y = -6 + 4s Divide each side by '-3'. y = 2 + -1.333333333s Simplifying y = 2 + -1.333333333s
| 20x=-80 | | -6y^2=-54 | | [-4g+2]=8 | | -4(6r-7)=35 | | (54x+65y)+(-11x+45y)= | | 4x+44=-19+x | | 3(x+5)=2(2x+11) | | (2x-5)(x-7)=0 | | 6(4w+8)=8 | | 10x+10=-40 | | X-9(3-x)=5+10x | | -7(2t+10)=-42 | | 8(2-p)=27 | | 3(f-9)=-30 | | (14x+6y)+(48x+34y)= | | 6+55x=44x+9 | | 8w+4x=5w-6x | | -4a+7=-17 | | [-5x-2]=8 | | 3*x-18=(x+3)*(x-3)*2+x^2+3*x+9 | | (50x+51y)-(-29x+3y)= | | -3(2x+9)+9= | | 12t-5=12t+5 | | X^5-2x^4+4x^2-5x+5= | | 19/5+5y=10y-1/5 | | 4*x+x=88 | | [2x-6]-4=26 | | v^2=8v+2 | | 4*x=88 | | 3*x-18=2*x^2-18+x^2+3*x+9 | | 5x+12-4x-14=3 | | 5y-10+y+48=5y+40-1y |